Study on Gas Adsorption Properties (N2, H2, O2, NO, NO2, CO, CO2, SO2, H2S, H2O and NH3) on the O-vacancy-containing Sc2CO2 Monolayer - Khang, Pham Dinh; Hai, Luong Le; Hong, Nguyen Thi Tham; Tuan, Vu Van (VNU Journal of Science: Mathematics - Physics, 2022)
In this work, we have studied the (N 2 , H 2 , O 2 , NO, NO 2 , CO, CO 2 , SO 2 , H 2 S, H 2 O, and NH 3 ) gases adsorption properties on the O-vacancy-containing Sc 2 CO 2 monolayer by first-principles calculations. We have determined the preferred adsorption positions and the structural features of the O-vacancy-containing Sc 2 CO 2 monolayer after adsorption of different gas molecules. The adsorption energy and charge transfer from the monolayer to the gas molecules have been calculated. The calculated results show that H 2 , N 2 , NH 3 , H 2 S and H 2 O molecules are physisorbed, while CO 2 , CO, NO 2 , NO, O 2 and SO 2 molecules are chemisorbed in the neighboring area of the O-vacancy of the Sc 2 CO 2 monolayer. The existence of the O-vacancy significantly enhances the CO and CO 2 adsorption intensity of the defect Sc 2 CO 2 monolayer compared to the original Sc 2 CO 2 monolayer. Our results show that the O-vacancy-containing Sc 2 CO 2 monolayer can be used for detecting NO gas  as a resistive sensor.